KAVRAMSAL DİZİN (THESAURUS) : YAPISI KULLANIMI VE HAZIRLANMASI - Aytaç Yıldızeli (Türk Kütüphaneciliği)
Thesauri of scientific terminology are indispensable tools for purposes of information retrieval serviees and indexing. The extent of a thesaurus in an area of scientific knowledge should depend upon a number of decisions concerning the type; amount and level of information on one side, and user qualifications and financial resources available on the other. Bearing these constraints in mind thesaurus contraction can be achieved by employing spercial metbods which lead to special structures. Thesaurus preparation according to ISO Standard 2788 has been reviewed ;:s an aid to probable designers of Turkish thesauri.